2D Graphene-TiO2 Composite and Its Photocatalytic Application in Water Pollutants - Zhou, Xin; Zhang, Xian; Wang, Yuemei; Wu, Zhen (Frontiers in Energy Research, 2021)
To solve the global water shortages and serious water pollution problems, research on semiconductor photocatalysts has generated significant research attention. The degradation of pollutants by titanium dioxide (TiO2) exceeds other semiconductor materials. However, its wide bandgap restricts the photocatalytic reaction under visible light. The large specific surface area and good thermal conductivity of graphene yielded an effective graphene-TiO2 catalyst combination effective under visible light. 2D graphene-TiO2 composites (2D-GTC) have shown promise, so a study of the preparation methods, mechanism and catalytic effect of different pollutants on this material was undertaken. In this current review, the characteristics of different graphene and TiO2 composites and their preparation methods, as well as the effects of different synthesis methods on the catalyst are introduced. The reaction mechanism of 2D-GTC catalysts, the degradation effects of different pollutants in water are all reviewed.